Reasons for encounter and diagnosis in patients seen in Frances Baard District public primary care: a prospective cross sectional study - Yogolelo, Willy Bulambo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2011.